URETHRAL INJURY IN REGIONAL HOSPITAL IN THE BPJS ERA: A CASE REPORT - Muhammad Omar R; Muhammad Taufiq Reza (Indonesian Journal of Urology, 2023)
ABSTRACT Objective: To present a case of urethral injury treated in a male adult. Case(s) Presentation: A 48 year old Asian male patient previously involved in a motor vehicle accident presented to the hospital with a chief complaint of pain and bleeding from the genitalia. On examination, it is revealed bleeding from the urethral meatus, pain in touch, palpable bladder, high riding prostate, and a butterfly-shaped bruising on the perineum. X-ray examination demonstrated soft tissue mass in the right scrotal region. The patient is diagnosed with urethral rupture with urinary retention and then underwent ultrasonography-guided cystostomy and perineal hematoma evacuation. The patient is followed-up 1 month later with a complaint of difficulty in voiding and erectile dysfunction. The patient is then diagnosed with urethral stricture and underwent direct vision urethrotomy. Discussion: Urethral injury is a rare type of injury of genitourinary trauma that may cause long term morbidity such as strictures, incontinence, impotence, and infertility. Urethral injury can be classified into posterior urethral injury which is associated with pelvic fracture and anterior urethral injury which is associated with blunt trauma. The gold standard of radiographic examination in urethral injury is dynamic retrograde urethrography. Prompt diagnosis, staging, and selecting intervention must be done for minimalizing complications. Sequelae may also develop which also affects quality of life. The usage of universal health coverage such as BPJS in In Indonesia can increase the accessibility of medical treatment. Conclusion: Urethral injury is a rare injury that requires prompt and careful management to minimize complications and increase the patient’s quality of life. Keywords: Urethral Injury, urethrotomy, urethral stricture.